Fin du Temps et Retour à l'Origine (Aspects de Vimamologie duodécimaine VI) - Mohammad Ali Amir-Moezzi (Revue des Mondes Musulmans et de la Méditerranée)
The aim of this study is the analysis of relations between cosmology and eschatology in Twelver Shiismaccording to the early corpus of Imâmite traditions and their latest exegesis. These relations seem to reveal some aspects still more or less unknown of Twelver messianism. The study is composed of two parts. First, it deals with the correspondence between universal eschatology and the important cosmological tradition of « the Armies of Intelligence and Ignorance ». Secondly, it studies the correspondence between individual eschatology and the series of traditions about the creation of worlds, their inhabitants and their roles. The examination of these relations seems to show, as some philosophical and mystical exegesis have underlined, that the Twelver Shiite vision of the world rests, like other initiatic traditions with mythical language, on the triptych of original purity, the invasion of evil and the final return to the origin.